A MEN1 Patient Presenting With Multiple Parathyroid Adenomas and Transient Hypercortisolism: A Case Report and Literature Review - Chen, Fuqiong; Xu, Qinqin; Yue, Wenzhu; Yu, Xuefeng; Shao, Shiying (Frontiers in Endocrinology, 2022)
Background: Multiple endocrine neoplasia type 1 (MEN1) is a hereditary endocrine syndrome caused by mutations in MEN1 tumor suppressor gene. Case presentation: A 53-year-old Chinese female was admitted to Division of Endocrinology, Tongji Hospital, for hypercalcemic crisis. Increased level of parathyroid hormone (PTH) was confirmed by laboratory tests, and imaging examination showed multiple parathyroid adenomas. Based on gene analysis, the patient was diagnosed as MEN1 associated hyperparathyroidism (HPT) by gene analysis with c.1378C>T (p.Arg460Ter) mutation in MEN1 gene. Her condition was complicated by transient hypercortisolism, mammary mass and uterine leiomyoma. After subtotal parathyroidectomy, PTH and serum calcium levels returned to normal. Conclusion: HPT with multiple parathyroid adenomas is an indication of MEN1 gene mutation. Serum cortisol and its circadian rhythm can be abnormal in the presence of hypercalcemia and high PTH. These parameters can return to normal after parathyroidectomy.